2006
DOI: 10.1007/s10750-006-0193-1
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of periphytic desmids in shallow softwater lakes in Belgium

Abstract: At 6 sites in 5 mesotrophic softwater lakes in the wetland Zwart Water (Belgium), periphyton samples were collected on different substrates ranging from macrophytes to mosses and sandy sediment. Significant differences between substrates were observed at 5 out of 6 sites studied. The differences between the substrates, however, could not be related to known effects of these substrates on their chemical environment (e.g., excretion of H + ions, CO 2 or allelopatic substances) nor to their morphology. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The results reported in the literature demonstrated strong affects of habitat structure and architecture of macrophyte leaf or stem on the spatial distribution and taxonomic composition of aquatic organisms (Duggan et al, 2001;Mieczan, 2007;Pals et al, 2006). Macrophytes strongly influence protozoan species composition by modifying protozoan food availability and increasing the spatial heterogeneity (Biyu, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results reported in the literature demonstrated strong affects of habitat structure and architecture of macrophyte leaf or stem on the spatial distribution and taxonomic composition of aquatic organisms (Duggan et al, 2001;Mieczan, 2007;Pals et al, 2006). Macrophytes strongly influence protozoan species composition by modifying protozoan food availability and increasing the spatial heterogeneity (Biyu, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently the number of possible niches offered for a variety of periphytic species is enormous, so differences in species composition and density on different macrophytes are likely to occur (Messyasz, Kuczynśka-Kippen, 2006;Mieczan, 2007;Pals et al, 2006).…”
mentioning
confidence: 99%
“…Concerning periphyton community structure on different substrate types, comparative investigations have shown that its attributes may be influenced by natural versus artificial substrates (Cattaneo & Amireault, 1992;Albay & Akcaalan, 2003;Vadeboncoeur et al, 2006;Ferragut et al, 2010), macrophyte architecture (Cattaneo et al, 1998) and surface roughness (Sousa & Ferragut, 2012). Specifically, the few studies on Zygnematophyceae algae available in the literature, which are focused on macrophytes and/or sandy sediments (Pals et al, 2006;Mutinová et al, 2016), have suggested that substrate influence is relatively low and varies with sites.…”
Section: Introductionmentioning
confidence: 99%
“…In freshwater benthic habitats, data on small-scale algal differentiation are less numerous. Recent studies concentrated on regional or large-scale processes of individual catchment areas (CHARLES et al, 2006), water bodies (PALS et al, 2006) or running waters (e.g., PASSY, 2001;SOININEN, 2005). The spatial organization of benthic invertebrate communities in two oligotrophic lakes was characterized by STOFFELS et al (2005).…”
Section: Introductionmentioning
confidence: 99%